Behavior of egg production in generations of Turquino hens from eggs classified as "not suitable" for incubation - Batista Casacó, Aimé Rosario (2026)
To demonstrate that second-generation Turquino pullets, derived from "non-standard" eggs, had similar performance to their progenitors (first generation) in egg production, a study was conducted with 2,000 pullets (1,000 for each treatment under study, from the incubation of "non-standard" eggs) from Unit #33 Antonio Maceo of the National Poultry Combine Companies (UECAN). A completely randomized design was used to evaluate the treatments, and correlations were established between different statistics to analyze relationships between variables: onset of laying (5 %), peak of laying, percentage of egg production at the peak of laying, and persistence of egg production. The animals were reared on the floor throughout the experiment (39 weeks). Regression equations for the studied curves were obtained using Curve Expert 1.3. The relationship of the egg production curves was established for each generation using a 6th-degree polynomial. The Chi-square test evaluated the independence or association between the variables used. The second-generation pullets showed similar productive performance to their first-generation progenitors, demonstrating the potential use of these eggs in the production of Turquino hens in Cuba. The similarity in egg production in the second generation was comparable to the first generation and the established typical curve. IBM SPSS Statistics version 24 – 2016 was used.